Public Service Commission of Malaysia / Nurul Hidayah Razim - Razim, Nurul Hidayah (2017)
This chapter focused on the introduction of the organization which is Public Services Commission of Malaysia (PSC). It had explained the function of the organization as well as the organization’s roles. This chapter continues with stated the organization’s vision, mission and motto. In addition, it also shows the organizational structure of Public Services of Commission and will discussed the client charter ofthe organisation.